2017
DOI: 10.1590/2446-4740.07716
|View full text |Cite
|
Sign up to set email alerts
|

Power amplifier circuits for functional electrical stimulation systems

Abstract: Introduction: Functional electrical stimulation (FES) is a technique that has been successfully employed in rehabilitation treatment to mitigate problems after spinal cord injury (SCI). One of the most relevant modules in a typical FES system is the power or output amplifier stage, which is responsible for the application of voltage or current pulses of proper intensity to the biological tissue, applied noninvasively via electrodes, placed on the skin surface or inside the muscular tissue, closer to the nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…Studies have revealed that a square pulse is the most efficient, because it avoids an accommodation of the membrane. Symmetrically compensated biphasic pulses are generally recommended because they allow electrochemical imbalances that produce tissue damage to be avoided [4,22]. As for the wave profile, a trapezoidal shape (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that a square pulse is the most efficient, because it avoids an accommodation of the membrane. Symmetrically compensated biphasic pulses are generally recommended because they allow electrochemical imbalances that produce tissue damage to be avoided [4,22]. As for the wave profile, a trapezoidal shape (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Monophasic pulses create charge imbalances because of a unidirectional current flow. By contrast, biphasic pulses allow the application and removal of electrical charges to and from the tissue, and thus the majority of neuroprostheses use biphasic pulses [22].…”
Section: Fes Techniquementioning
confidence: 99%
“…A voltage increase can be achieved through some methods, including boost transformers at the output stage—a topology that is still often used, despite increasing the size and weight of the circuit as well as causing electromagnetic interference [ 26 ]. A more modern topology is the use of switch boost converters.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the design of the stimulation electronics used in the SMARTmove system. A review of stimulation electronics output stages for FES has been carried out by Souza [13]. The applied stimulation can be grouped into two general categories: monophasic where the stimulation pulses only have one polarity; and biphasic where the stimulation pulses have both positive and negative polarities.…”
Section: Introductionmentioning
confidence: 99%